2004
DOI: 10.1038/sj.emboj.7600402
|View full text |Cite
|
Sign up to set email alerts
|

Suz12 is essential for mouse development and for EZH2 histone methyltransferase activity

Abstract: SUZ12 is a recently identified Polycomb group (PcG) protein, which together with EZH2 and EED forms different Polycomb repressive complexes (PRC2/3). These complexes contain histone H3 lysine (K) 27/9 and histone H1 K26 methyltransferase activity specified by the EZH2 SET domain. Here we show that mice lacking Suz12, like Ezh2 and Eed mutant mice, are not viable and die during early postimplantation stages displaying severe developmental and proliferative defects. Consistent with this, we demonstrate that SUZ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
721
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 816 publications
(764 citation statements)
references
References 30 publications
39
721
1
3
Order By: Relevance
“…(12,41). Previous studies have also shown that, although it contains the Su(var)3-9, enhancer of zeste, and trithorax domain for HMTase activity for H3K27, to gain catalytic activity EZH2 requires association with SUZ12 and EED (41). Therefore, the depletion of the PRC2 complex components due to treatment with HA-HDI or EZH2 siRNA results in the attenuation of HMTase activity of EZH2 and decreased trimethylation and dimethylation of H3K27 in the leukemia cells.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…(12,41). Previous studies have also shown that, although it contains the Su(var)3-9, enhancer of zeste, and trithorax domain for HMTase activity for H3K27, to gain catalytic activity EZH2 requires association with SUZ12 and EED (41). Therefore, the depletion of the PRC2 complex components due to treatment with HA-HDI or EZH2 siRNA results in the attenuation of HMTase activity of EZH2 and decreased trimethylation and dimethylation of H3K27 in the leukemia cells.…”
Section: Discussionmentioning
confidence: 98%
“…Total histone H3 levels were used as a loading control. (12,41). Previous studies have also shown that, although it contains the Su(var)3-9, enhancer of zeste, and trithorax domain for HMTase activity for H3K27, to gain catalytic activity EZH2 requires association with SUZ12 and EED (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30][31] EZH2, a component of PRC2, is a histone methyltransferase that carries out the methylation of lysine 27 of histone H3. 32,33 Methylation of H3K27 recruits additional repressive complexes such as PRC1, which adds an additional level of repression that is propagated. 27,28,34,35 The DNA molecule can also be modified at the 5' position of cytosine rings present in CG dinucleotide sequences by addition of a methyl group.…”
Section: Metabolic Pathways and Mechanisms Of Regulationmentioning
confidence: 99%
“…SUZ12 is essential for the integrity of the PRC2 complexes, the stability of EZH2, and hence the HMTase activity of the complex [14,17] . It contains a C-terminal Vrn2-Emf2-Fis2-SUZ12…”
Section: Introductionmentioning
confidence: 99%